2019
DOI: 10.1016/j.ebiom.2019.03.016
|View full text |Cite
|
Sign up to set email alerts
|

Exosomal transfer of miR-1238 contributes to temozolomide-resistance in glioblastoma

Abstract: Background Although temozolomide (TMZ) resistance is a significant clinical problem in glioblastoma (GBM), its underlying molecular mechanisms are poorly understood. In this study, we identified the role of exosomal microRNAs (miRNAs) from TMZ-resistant cells as important mediators of chemoresistance in GBM cells. Methods Exosomes were isolated from TMZ-resistant GBM cells and characterized via scanning electron microscopy (SEM). Expression levels of miR-1238 in GBM cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
112
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 145 publications
(114 citation statements)
references
References 49 publications
(46 reference statements)
1
112
0
1
Order By: Relevance
“…For example, miR-181b regulated the chemosensitivity of glioma to temozolomide by targeting Bcl-2 and EGFR [123,124]. Also, exosomal miR-1238 may confer chemoresistance in the tumor microenvironment, indicating that circulating miR-1238 acted as a promising therapeutic target for TMZ resistance in GBM [125]. Lei et al demonstrated that down-regulated hsa_circ_ 0076248 could remarkably promote the TMZ chemotherapy sensitivity via sponge miR-181a, which could suppress the expression of silent information regulator 1 (SIRT1) [52].…”
Section: Circrnas Are Potential Novel Biomarkers For Diagnosis and Prmentioning
confidence: 99%
“…For example, miR-181b regulated the chemosensitivity of glioma to temozolomide by targeting Bcl-2 and EGFR [123,124]. Also, exosomal miR-1238 may confer chemoresistance in the tumor microenvironment, indicating that circulating miR-1238 acted as a promising therapeutic target for TMZ resistance in GBM [125]. Lei et al demonstrated that down-regulated hsa_circ_ 0076248 could remarkably promote the TMZ chemotherapy sensitivity via sponge miR-181a, which could suppress the expression of silent information regulator 1 (SIRT1) [52].…”
Section: Circrnas Are Potential Novel Biomarkers For Diagnosis and Prmentioning
confidence: 99%
“…Exosomes containing mRNA and miRNA were first reported by Valadi et al (54). Numerous studies have since demonstrated the existence of various small ncRNA species (in addition to miRNA, lncRNA and mRNA) in exosomes (55)(56)(57)(58). Subsequently, Li et al (6) reported the existence of a large quantity of circRNAs in exosomes.…”
Section: Exosomal Circrnas and Their Sorting Mechanismsmentioning
confidence: 99%
“…Similarly, it has been elucidated that hypoxia-induced autophagy can affect cell mobility, tumor progression and chemosensitivity in GBM, via modulating the HIF-1α/ miR-224-3p/ATG5 axis [123]. While, miR-1238 is upregulated in TMZ-resistant GBM cells, and the silencing of miR-1238 can improve chemosensitivity through directly targeting the CAV1/epidermal growth factor receptor (EGFR) pathway [124]. And for DDP treatment, miR-501-3p can sensitize GBM to DDP-induced proliferation arrest and apoptosis by targeting N-myc (MYCN) [125].…”
Section: Glioblastoma (Gbm)mentioning
confidence: 99%